Employment Differentiation, Minimum Wages and Firm Exit (2021)
The economic literature acknowledges that labor markets can often be described by monopsonistic competition. In such a structure, employers have market power and in the long run, zero profits due to the free entry and exit of firms. This article builds a model to analyze the role of minimum wages when employment is differentiated. It shows that first best and second best minimum wages can increase employment and improve efficiency by reducing market power, at the expense of having firm exit, higher concentration among employers, and less employment variety. As such, this article can provide insights on the higher firm exit rates observed among new, small and lower productivity firms.